Fatigue Strength Estimation of Ductile Cast Irons Containing Solidification Defects - Camilla Ronchei (Metals, 2022)
The goal of the present paper is to discuss the accuracy and reliability of a procedure for the fatigue strength estimation of defective metals by considering some experimental data available in the literature. In particular, the fatigue behaviour of three ductile cast irons (DCIs) containing solidification defects (i.e., micro-shrinkage porosity) is simulated through the above a procedure, based on the joined application of the <semantics><msqrt>area</msqrt></semantics>-parameter model and the Carpinteri et al. multiaxial fatigue criterion. The fatigue strength of such DCIs subjected to both uniaxial (rotating bending or torsion) and biaxial (combined tension and torsion) cyclic loading is evaluated and compared with the experimental results.